UPAYA MENINGKATKAN KEMAMPUAN MENGENAL ANGKA MELALUI PERMAINAN DADU BOLA MINI WARNA-WARNI PADA ANAK USIA 3-4 TAHUN DI KB DARUT TAUHID KREJENGAN PROBOLINGGO - Suci Rusmini; Hendrik Siswono; Wedya Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is entitled "Efforts to Improve Number Recognition Skills Through Colorful Mini Ball Dice Games in 3-4 Year Old Children at KB Darut Tauhid Krejengan Probolinggo". The problem underlying this study is the low ability of children to recognize numbers. Based on the results of initial observations, most children aged 3-4 years at KB Darut Tauhid have difficulty distinguishing number shapes, connecting number symbols with the number of objects, and are less motivated in learning to count. This is because the methods used are still conventional and the lack of variety of learning methods that involve direct experience. The purpose of this study is to improve number recognition skills through Colorful Mini Ball Dice Games in 3-4 year old children at KB Darut Tauhid Krejengan Probolinggo. The research method used is Classroom Action Research (CAR) model Kemmis and McTaggart which was implemented in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The research subjects were 13 children in the playgroup aged 3-4 years at KB Darut Tauhid. Data collection techniques used observation and documentation, while data analysis techniques were carried out descriptively qualitatively and quantitatively through the calculation of the percentage of children's developmental achievements. The expected outcomes of this research are an increase in children's ability to recognize numbers through interesting play activities, the arrangement of learning steps using colorful mini ball dice media, and recommendations for creative learning strategies for PAUD teachers. The results of the research are expected to be a reference in the development of early arithmetic learning methods in PAUD institutions, especially through a play approach.